(untitled) (The Pakistan Development Review, 1988)
In the last decade, Pakistan’s external debt obligations have risen to an unprecedented level. This is despite the fact that the country had been able to borrow on concessional terms from international organizations and foreign governments unlike many other developing countries. The situation has raised concern about the viability of the strategy of excessive dependence on foreign sources and the problems it poses for sustainable growth. Between 1970 and 1980 Pakistan’s external debt grew at an average rate of 11.3 percent. Althol1gh, during the Eighties it has grown at a much slower rate, i.e. 2.37 percent, but by 1986-87 the level of total external debt had reached more than 12 billion U.S. dollars. A notable feature of this change has been that since the mid-Seventies the debt service payments have increased at a much faster rate compared with the outstanding debt.